Sulfonated C4N nanosheet, preparation method thereof and solid electrolyte

By using sulfonated C4N nanosheets as nanofillers in PEO electrolytes, the problem of insufficient ionic conductivity and mechanical properties of PEO electrolytes at room temperature is solved, rapid conduction of lithium ions and uniformity of electrolytes are achieved, and lithium metal is improved Battery safety and performance.

CN119320124AActive Publication Date: 2025-01-17SUN YAT SEN UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411832069.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-01-17
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The existing PEO solid electrolytes have insufficient ionic conductivity and mechanical properties at room temperature, and the compatibility of nanofillers and electrolyte interfaces leads to uneven lithium ion flux, affecting the safety and performance of lithium metal batteries.

Method used

The dispersion of nanofillers and electrolytes is improved by interacting with the PEO chain segments, and the dissociation energy barrier of lithium salt is reduced through the -SO3H functional group, thereby enhancing the ionic conductivity and Number of migrations.

Benefits of technology

The uniform dispersion of sulfonated C4N nanosheets in PEO electrolyte is achieved, the conduction capacity of lithium ions and the mechanical properties of the electrolyte are improved, and the safety and specific energy density of solid-state lithium metal batteries are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320124A_ABST
    Figure CN119320124A_ABST
Patent Text Reader

Abstract

The invention discloses a sulfonated C4N nanosheet, a preparation method thereof and a solid electrolyte. The composite solid electrolyte contains polyoxyethylene, a nanofiller and a lithium salt, and the nanofiller is a sulfonated C4N nanosheet. According to the composite solid electrolyte disclosed by the invention, a small amount of sulfonated C4N nanosheets are creatively adopted as the organic nanofiller, and-SO3H functional groups of the sulfonated C4N nanosheets can interact with ether oxygen on a PEO chain segment, so that the nanofiller is well compatible with a PEO polymer on a molecular level; sulfonated C4N nanosheets can be uniformly dispersed in a polymer matrix, and the problem that inorganic nanofiller is prone to agglomeration is solved. More amorphous regions can be generated by adding a proper amount of sulfonated C4N nanosheets, so that the movement capability of polymer chain segments is improved, and rapid conduction of lithium ions is facilitated. In addition, the sulfonated C4N nanosheets are added, so that the PEO electrolyte can be well toughened, and better thermal stability is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid electrolytes, and in particular to a sulfonated C 4 N nanosheets, preparation methods and solid electrolytes thereof. Background Art

[0002] Solid-state lithium metal batteries use solid electrolytes with high specific energy and high safety, and are the next generation of batteries with great application prospects. Among many solid electrolytes, polyethylene oxide (PEO) can dissolve lithium salts well and is compatible with the electrode interface. It is currently the most studied type of polymer solid electrolyte. The transport mechanism of lithium ions in PEO electrolytes mainly relies on the coordination with the ether oxygen on the PEO chain segments and the relaxation movement of the chain segments. However, PEO is easy to crystallize at room temperature, which leads to insufficient chain segment movement and usually exhibits poor ionic conductivity (< 10 −6 S cm −1 ) and a low ion migration number (0.2 ~ 0.4). In addition, due to the poor mechanical properties of PEO, the solid-state lithium metal battery assembled by solid state will be punctured by lithium dendrites during long-term cycling, posing serious safety hazards. Therefore, it is necessary to develop a simple and practical design method to alleviate the above dilemma.

[0003] Studies have shown that adding nanofillers to PEO electrolytes can improve ionic conductivity, ion migration number and mechanical strength. In general, inorganic nanofillers can weaken the interaction between PEO and lithium ions, promote the dissociation of lithium salts, and reduce the crystallinity of polymers to produce more amorphous micro-regions, which is conducive to better lithium ion conduction. However, poor compatibility of inorganic nanofillers / PEO interfaces can cause serious phase separation in solid electrolytes. When the content of inorganic nanofillers (> 5 wt%) is high, inorganic nanofillers tend to agglomerate, which will lead to uneven lithium ion flux and affect the effective transmission of lithium ions in polymer electrolytes. In contrast, a small amount of functional organic nanofillers is used to circumvent the above problems. They can interact with PEO polymers at the molecular level, which can not only improve the dispersibility of nanofillers in polymers, but also ensure that the nanofiller / PEO interface has good compatibility, while improving the mechanical properties, ionic conductivity and ion migration number of solid electrolytes, so that PEO electrolytes can be effectively used in high-safety, high-specific-energy lithium metal batteries. Summary of the invention

[0004] Based on this, with respect to the PEO solid electrolyte in the prior art, how to improve the ionic conductivity and ion migration number of the electrolyte, and avoid the technical problems of poor compatibility between the nanofiller and the electrolyte interface and easy agglomeration of the nanofiller, the purpose of the present invention is to provide a new sulfonated C 4N nanosheet materials are used as organic nanofillers and composite solid electrolytes prepared therefrom, thereby overcoming the aforementioned technical problems.

[0005] To achieve the above objectives, the present invention adopts the following technical solutions.

[0006] A sulfonated C 4 N nanosheets are prepared by the following method: (1) Dissolving 2,3,6,7,10,11-hexaaminotriphenyl and cyclohexanehexatone in a first solvent to prepare a first reaction solution; then deoxygenating the first reaction solution, and then subjecting it to a hydrothermal reaction, and collecting the solid by vacuum filtration; washing the solid and dispersing it in a second solvent to obtain a dispersion; subjecting the dispersion to Soxhlet extraction, and drying to obtain a dark red C 4 N powder; (2) The above C 4 The N powder is annealed, then mixed with acid solution and ultrasonicated, filtered after ultrasonication, and washed and filtered to obtain C 4 N nanosheets; (3) The obtained C 4 N nanosheets are dispersed in chloroform, and chlorosulfonic acid is added and mixed evenly; then, the mixture is heated and refluxed, and a suspension is obtained after cooling; the suspension is washed to a neutral pH, and then filtered and dried to obtain sulfonated C 4 N nanosheets.

[0007] As a preference, in the above-mentioned sulfonated C 4 In the N nanosheet, the mass ratio of 2,3,6,7,10,11-hexaaminotriphenyl and cyclohexanehexanone in step (1) is 1:0.5-0.8; the first solvent is selected from at least one of N, N-dimethylformamide, N-methyl-2-pyrrolidone, dimethyl sulfoxide and diethyl diether; the deoxygenation treatment is performed by vacuumizing by cooling with liquid nitrogen; the second solvent is selected from at least one of water, methanol, ethanol and N-methylpyrrolidone; and the conditions of the hydrothermal reaction are: calcination at 160-200°C for 6-12 h.

[0008] As a preference, in the above-mentioned sulfonated C 4 In the N nanosheet, the acid solution in step (2) is selected from at least one of hydrochloric acid, acetic acid and sulfuric acid; the annealing treatment conditions are: calcination at 400-600°C for 6-12 h; and the heating reflux conditions in step (3) are: reflux at 60-90°C for 6-10 h.

[0009] A composite solid electrolyte comprising polyethylene oxide, nanofiller and lithium salt, wherein the nanofiller is the sulfonated C 4 N nanosheets.

[0010] Preferably, in the composite solid electrolyte, the molar ratio of polyethylene oxide to lithium salt LiTFSI is 16:1; 4 The mass ratio of N nanosheets to polyethylene oxide is 0.5~2:100.

[0011] Preferably, in the above composite solid electrolyte, the weight average molecular weight of the polyethylene oxide is 600,000 g / mol.

[0012] Preferably, in the above composite solid electrolyte, the lithium salt is selected from LiTFSI, LiClO 4 、LiPF 6 , LiBF 4 One or a mixture of several of them.

[0013] The preparation method of the composite solid electrolyte comprises the following steps: Polyethylene oxide, lithium salt and sulfonated C 4 N nanosheets are added to an organic solvent according to a stoichiometric ratio, dispersed evenly to obtain a slurry, and then poured onto a polyvinylidene fluoride mold. The slurry is placed in a glove box for 24 hours for preliminary drying, and then dried in a vacuum drying oven at 50°C for 24 to 48 hours to obtain a composite solid electrolyte.

[0014] Preferably, in the above-mentioned method for preparing the composite solid electrolyte, the organic solvent is one or a mixture of several of acetonitrile, chloroform, tetrahydrofuran, N,N-dimethylformamide, N-methyl-2-pyrrolidone and dimethyl sulfoxide.

[0015] An all-solid-state lithium battery comprises a positive electrode material, a lithium metal negative electrode, and a solid electrolyte arranged between the positive electrode and the negative electrode, wherein the solid electrolyte is the composite solid electrolyte mentioned above.

[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) The composite solid electrolyte of the present invention innovatively uses a small amount of sulfonated C 4 N nanosheets as organic nanofillers, sulfonated C 4 N nanosheets of -SO 3 The H functional group can interact with the ether oxygen on the PEO chain segment, making the nanofiller well compatible with the PEO polymer at the molecular level. 4 N nanosheets can be evenly dispersed in the polymer matrix, overcoming the problem of inorganic nanofillers being easily agglomerated. 4 N nanosheets can produce more amorphous regions to improve the mobility of polymer segments, which is beneficial to promote the rapid conduction of lithium ions.

[0017] (2) C4 N nanosheets are a new type of two-dimensional layered polymer material with a carbon-nitrogen ratio of 4:1. Through sulfonation treatment, -SO 3 H functional group, thereby obtaining sulfonated C 4 N polymer materials. In sulfonated C 4 In N materials, N atoms have electronegativity, which gives C 4 The unique electronic structure of N skeleton, -SO 3 The H functional group can couple lithium ions and repel lithium salt anions. The two synergistically reduce the dissociation barrier of lithium salts in PEO polymer electrolytes, generate more free lithium ions, and are beneficial to enhance the ionic conductivity and ion migration number of solid electrolytes, thereby achieving uniform lithium ion flux and ultimately effectively inhibiting the growth of lithium dendrites. 4 The N skeleton can act as a highway for lithium ion conduction, improving the transport kinetics of lithium ions in PEO electrolytes. 4 N nanosheets can effectively toughen PEO electrolyte and obtain better thermal stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Sulfonated C 4 Transmission electron microscopy image of N nanosheets; Figure 2 Sulfonated C 4 Infrared spectrum of N nanosheets; Figure 3 The scanning electron microscope images of the solid electrolytes of Example 1 and Comparative Example 1 are shown; Figure 4 Ionic conductivity of the solid electrolytes of Example 1, Example 2 and Comparative Examples 1-3 at 30° C. and 60° C.; Figure 5 The electrochemical stability window of the solid electrolytes of Example 1, Example 2 and Comparative Examples 1-3; Figure 6 It is a crystallization peak curve diagram of the solid electrolyte of Example 1 and Comparative Example 1; Figure 7 The rate performance of the lithium iron phosphate battery with solid electrolyte of Example 1 and Comparative Example 1 at 60°C; Figure 8 The cycle performance of lithium iron phosphate batteries with solid electrolytes of Example 1 and Comparative Example 1 at 60°C. DETAILED DESCRIPTION

[0019] The temperature parameters in the present invention, if not specifically limited, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the precision range controlled by the instrument.

[0020] In the present invention, "sulfonated C 4 N nanosheets" refers to Figure 1 The sheet-like polymer material shown in .

[0021] The "ionic conductivity" in the present invention refers to the conductivity of lithium ions in a solid polymer electrolyte in a solid-state battery.

[0022] Unless otherwise specified, the frequency of "ultrasonic treatment" in the present invention is 1000 Hz and the time is 10 minutes.

[0023] It can be understood that organic nanomaterials refer to nano-sized sulfonated C 4 The specific macroscopic morphology of the N nanosheet is not limited, and can be in the form of a nanosheet.

[0024] The present invention provides a novel sulfonated C 4 The preparation method of N nanosheet material comprises the following steps: S1: Dissolve 2,3,6,7,10,11-hexaaminotriphenyl and cyclohexanehexatone in a first solvent to prepare a first reaction solution, deoxygenate the mixed solution, perform a hydrothermal reaction, and collect the solid by vacuum filtration. Wash the solid and disperse it in a second solvent, perform Soxhlet extraction on the dispersion, and dry it to obtain a dark red block C. 4 N powder.

[0025] S2: The block C 4 The N polymer is annealed, then mixed with acid solution and subjected to ultrasonic treatment, the acid solution is filtered, washed and filtered to obtain C 4 N nanosheets. 4 N nanosheets were dispersed in chloroform, and chlorosulfonic acid was added and mixed evenly. The mixed solution was heated to reflux and cooled to obtain a suspension. The suspension was washed to a neutral pH, and then filtered and dried to obtain sulfonated C 4 N nanosheets.

[0026] Further, in step S1: In some examples, the mass ratio of 2,3,6,7,10,11-hexaaminotriphenyl and cyclohexanone is 1:(0.5-0.8). Specifically, the mass ratio includes but is not limited to: 1:(0.5, 0.6, 0.7, 0.8).

[0027] In some examples, the first solvent is selected from at least one of N,N-dimethylformamide, N-methyl-2-pyrrolidone, dimethyl sulfoxide and diethyl diether. The first solvent needs to be deoxygenated before use, that is, nitrogen is introduced for 10 to 15 minutes, specifically, the time includes but is not limited to: 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes.

[0028] In some examples, the second solvent is at least one of water, methanol, ethanol and N-methylpyrrolidone.

[0029] The conditions of the hydrothermal reaction include: calcination at 160-200°C for 6-12 h. Specifically, the temperature of the hydrothermal reaction includes, but is not limited to, 160°C, 170°C, 180°C, 190°C, and 200°C. The reaction time includes, but is not limited to, 6h, 7h, 8h, 9h, 10h, 11h, and 12h.

[0030] Further, in step S2: In some examples, the acid is selected from at least one of hydrochloric acid, acetic acid, and sulfuric acid.

[0031] In some examples, the annealing conditions include: calcination at 400-600°C for 6-12 h. Specifically, the temperature of the hydrothermal reaction includes, but is not limited to, 400°C, 450°C, 500°C, 550°C, and 600°C. The reaction time includes, but is not limited to, 6h, 7h, 8h, 9h, 10h, 11h, and 12h.

[0032] In some examples, the heating reflux conditions include: reflux at 60-90°C for 6-10 h. The heating reflux temperature includes, but is not limited to, 60°C, 70°C, 80°C, and 90°C. The reaction time includes, but is not limited to, 6h, 7h, 8h, 9h, and 10h.

[0033] The present invention also provides a method for preparing a solid electrolyte, comprising the following steps: PEO polymer, lithium salt and sulfonated C 4 N nanosheets were added to the organic solvent according to the stoichiometric ratio, stirred evenly to obtain the slurry, and then poured onto the polyvinylidene fluoride mold, placed in a glove box for 24 h for preliminary drying, and then dried in a vacuum drying oven at 50 ° C for 24 h to obtain the polymer solid electrolyte. The molar ratio of PEO to lithium salt LiTFSI was 16:1 ([EO]:[Li + ]); Sulfonated C 4 The mass ratio of N nanosheets to PEO is (0.5~2):100.

[0034] In some examples, the organic solvent is one or a mixture of acetonitrile, acetone, tetrahydrofuran.

[0035] The present invention also provides a solid-state lithium metal battery, which comprises a positive electrode, a negative electrode, and a solid electrolyte disposed between the positive electrode and the negative electrode; the solid electrolyte is the polymer composite solid electrolyte as described above.

[0036] The following are specific examples.

[0037] Example 1: Preparation of composite solid electrolyte for lithium battery PEO with a weight average molecular weight of 600,000 g / mol, sulfonated C 4 N nanosheets and LiTFSI were ultrasonically dispersed in acetonitrile (the molar ratio of PEO to lithium salt LiTFSI was 16:1 ([EO] : [Li + ]); Sulfonated C 4 The mass ratio of N nanosheets to PEO is 1:100), and a slurry is obtained after being stirred evenly; then 10 mL of the slurry is measured and poured onto a polyvinylidene fluoride mold, and allowed to stand in a glove box for 24 h for preliminary drying, and then dried in a vacuum drying oven at 50°C for 24 h to obtain a composite solid electrolyte for lithium batteries.

[0038] Example 2: Preparation of composite solid electrolyte for lithium battery PEO with a weight average molecular weight of 600,000 g / mol, sulfonated C 4 N nanosheets and LiTFSI were ultrasonically dispersed in acetonitrile (the molar ratio of PEO to lithium salt LiTFSI was 16:1 ([EO] : [Li + ]); Sulfonated C 4 The mass ratio of N nanosheets to PEO is 2:100), and a slurry is obtained after being stirred evenly; then 10 mL of the slurry is measured and poured onto a polyvinylidene fluoride mold, and allowed to stand in a glove box for 24 h for preliminary drying, and then dried in a vacuum drying oven at 50°C for 24 h to obtain a composite solid electrolyte for lithium batteries.

[0039] Comparative Example 1: Preparation of composite solid electrolyte for lithium battery PEO and LiTFSI with a weight average molecular weight of 600,000 g / mol were ultrasonically dispersed in acetonitrile (the molar ratio of PEO to lithium salt LiTFSI was 16:1 ([EO] : [Li + ]), stir evenly to obtain a slurry; then measure 10 mL of the slurry, pour it onto a polyvinylidene fluoride mold, let it stand in a glove box for 24 h to allow it to dry initially, and then dry it in a vacuum drying oven at 50°C for 24 h to obtain a composite solid electrolyte for lithium batteries.

[0040] Comparative Example 2: Preparation of composite solid electrolyte for lithium battery PEO with a weight average molecular weight of 600,000 g / mol, graphene nanosheets, and LiTFSI were ultrasonically dispersed in acetonitrile (the molar ratio of PEO to lithium salt LiTFSI was 16:1 ([EO] : [Li +]); the mass ratio of graphene nanosheets to PEO is 1:100), and a slurry is obtained after being evenly stirred; then 10 mL of the slurry is measured and poured onto a polyvinylidene fluoride mold, and allowed to stand in a glove box for 24 h for preliminary drying, and then dried in a vacuum drying oven at 50°C for 24 h to obtain a composite solid electrolyte for lithium batteries.

[0041] Comparative Example 3: Preparation of composite solid electrolyte for lithium battery PEO, C 4 N nanosheets and LiTFSI were ultrasonically dispersed in acetonitrile (the molar ratio of PEO to lithium salt LiTFSI was 16:1 ([EO] : [Li + ]);C 4 The mass ratio of N nanosheets to PEO is 1:100), and the slurry is obtained after being stirred evenly; then 10 mL of the slurry is measured and poured onto a polyvinylidene fluoride mold, and allowed to stand in a glove box for 24 h for preliminary drying, and then dried in a vacuum drying oven at 50°C for 24 h to obtain a composite solid electrolyte for lithium batteries.

[0042] Performance Testing Test the lithium ion conductivity, thermal stability and electrochemical voltage window of the composite solid electrolyte.

[0043] Test the rate performance and cycle performance of solid-state lithium iron phosphate batteries.

[0044] The ionic conductivity of the obtained composite solid electrolyte is shown in Table 1.

[0045]

[0046] The composite solid electrolytes of Example 1 and Comparative Example 1 were applied to all-solid-state lithium iron phosphate batteries, and their rate performances are shown in Table 2.

[0047]

[0048] Conclusion: The data in Tables 1 and 2 show that the composite solid electrolyte obtained in Example 1 has the highest ionic conductivity and has better specific capacity and rate performance when applied to solid-state lithium metal batteries.

[0049] Figure 1 Sulfonated C 4 Transmission electron microscopy of N nanosheets shows that sulfonated C 4 N is in the form of nanosheets.

[0050] Figure 2 Sulfonated C 4 The infrared spectrum of N nanosheets shows that at 1039 cm -1The characteristic peaks correspond to the sulfonated functional groups.

[0051] Figure 3 The scanning electron microscope images of Example 1 and Comparative Example 1 show that Example 1 adds sulfonated C 4 When N is in nanosheet form, the surface of the solid electrolyte becomes smoother, indicating that the composite solid electrolyte has good interface compatibility with the electrode.

[0052] Figure 4 In combination with the data in Table 1, whether at 30°C or 60°C, Example 1 has lower electrochemical impedance and higher ionic conductivity, indicating that adding an appropriate amount of sulfonated C 4 N nanosheets can improve the ionic conductivity of composite solid electrolytes.

[0053] Figure 5 The electrochemical stability window of Example 1 and Example 2 is wider, which reflects the addition of sulfonated C 4 Advantages of N nanosheet composite solid electrolyte.

[0054] Figure 6 The temperature of Example 1 is lower than that of Comparative Example 1, indicating that the addition of sulfonated C 4 N nanosheets can destroy the order of the polymer matrix.

[0055] Figure 7 In combination with the data in Table 2, the rate performance of the lithium iron phosphate battery based on the composite solid electrolyte of Example 1 is better than that of Comparative Example 1.

[0056] Figure 8 The cycle performance of the lithium iron phosphate battery based on the composite solid electrolyte of Example 1 is better than that of Comparative Example 1.

Claims

1. A sulfonated C4N nanosheet, characterized in that Prepared by the following method: (1) dissolving 2,3,6,7,10,11-hexaaminotriphenyl and cyclohexanehexanone in a first solvent to prepare a first reaction solution; then deoxygenating the first reaction solution, performing a hydrothermal reaction, and collecting solids by vacuum filtration; washing the solids and dispersing them in a second solvent to obtain a dispersion, performing Soxhlet extraction on the dispersion, and drying to obtain dark red C4N powder; (2) annealing the C4N powder, mixing it with an acid solution and ultrasonicating it, filtering it after ultrasonication, washing it and filtering it to obtain C4N nanosheets; (3) dispersing the obtained C4N nanosheets in chloroform, adding chlorosulfonic acid and mixing evenly; then heating and refluxing, and cooling to obtain a suspension; The suspension was washed to a neutral pH, filtered and dried to obtain sulfonated C4N nanosheets.

2. The sulfonated C4N nanosheet according to claim 1, characterized in that: In step (1), the mass ratio of 2,3,6,7,10,11-hexaaminotriphenyl and cyclohexanone is 1:0.5-0.8; the first solvent is selected from at least one of N,N-dimethylformamide, N-methyl-2-pyrrolidone, dimethyl sulfoxide and diethyl diether; the deoxygenation treatment is performed by vacuumizing by cooling with liquid nitrogen; the second solvent is selected from at least one of water, methanol, ethanol and N-methylpyrrolidone; and the conditions of the hydrothermal reaction are: calcination at 160-200°C for 6-12 h.

3. The sulfonated C4N nanosheet according to claim 1, characterized in that: The acid solution in step (2) is selected from at least one of hydrochloric acid, acetic acid and sulfuric acid; the annealing treatment conditions are: calcination at 400-600° C. for 6-12 h; and the heating reflux conditions in step (3) are: reflux at 60-90° C. for 6-10 h.

4. A composite solid electrolyte comprising polyethylene oxide, nanofiller and lithium salt, characterized in that The nanofiller is the sulfonated C4N nanosheet according to claim 1.

5. The composite solid electrolyte according to claim 4, characterized in that: The molar ratio of polyethylene oxide to lithium salt LiTFSI is 16:1; the mass ratio of sulfonated C4N nanosheets to polyethylene oxide is 0.5~2:

100.

6. The composite solid electrolyte according to claim 4, characterized in that: The weight average molecular weight of the polyethylene oxide is 600,000 g / mol.

7. The composite solid electrolyte according to claim 4, characterized in that: The lithium salt is selected from one or a mixture of LiTFSI, LiClO4, LiPF6, and LiBF4.

8. A method for preparing the composite solid electrolyte according to claim 4, characterized in that The steps include: Polyethylene oxide, lithium salt and sulfonated C4N nanosheets are added to an organic solvent in a stoichiometric ratio, dispersed evenly to obtain a slurry, and then poured onto a polyvinylidene fluoride mold. The slurry is placed in a glove box for 24 hours for preliminary drying, and then dried in a vacuum drying oven at 50°C for 24 to 48 hours to obtain a composite solid electrolyte.

9. The method for preparing a composite solid electrolyte according to claim 8, characterized in that: The organic solvent is one of acetonitrile, chloroform, tetrahydrofuran, N,N-dimethylformamide, N-methyl-2-pyrrolidone and dimethyl sulfoxide, or a mixture of several thereof.

10. An all-solid-state lithium battery, comprising a positive electrode material, a lithium metal negative electrode, and a solid electrolyte disposed between the positive electrode and the negative electrode, characterized in that: The solid electrolyte is the composite solid electrolyte according to claim 4.

Citation Information

Patent Citations

  • C4N quantum dot material, preparation method thereof, and lithium-sulfur battery diaphragm

    CN113851696A

  • Two-dimensional covalent organic framework cobalt metal modified material for producing oxygen through efficient electro-catalytic decomposition of water

    CN114164459A

  • Hydroxylated COF flexible quasi-solid-state lithium battery diaphragm and lithium battery preparation method

    CN116470131A

  • Solid-state battery polymer electrolyte and preparation method and application thereof

    CN118970165A